Pengaruh Ukuran Perusahaan dan Leverage terhadap Tax Avoidance - Taslim Syahputra (Universitas Pamulang, 2023)
This research aims to test whether company size and leverage affect tax avoidance. This research is quantitative research with associative methods, the data used is secondary data. The data analysis method used is panel data regression processed using Eviews version 10. The population used in this research is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange in 2017 - 2021, totaling 98 companies. The samples used in this research were non-cyclical consumer sector companies listed on the Indonesian Stock Exchange in 2017-2022, where sampling used a purposive sampling method and 33 companies were obtained. The results of this research show that company size has no effect on tax avoidance, while leverage has an effect on tax avoidance